2009
DOI: 10.1186/1743-422x-6-133
|View full text |Cite
|
Sign up to set email alerts
|

Does the viral subtype influence the biennial cycle of respiratory syncytial virus?

Abstract: Background: The epidemic pattern of respiratory syncytial virus (RSV) is quite different in regions of Europe (biennial epidemics in alternating cycles of approximately 9 and 15 months) than in the Western Hemisphere (annual epidemics). In order to determine if these differences are accounted for by the circulation of different RSV subtypes, we studied the prevalence of RSV subtype A and B strains in Zagreb County from 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
6
19
2
6
Order By: Relevance
“…These results are consistent with the findings of others that RSV-A is not more severe than RSV-B. 44 We used real-time RT-PCR to quantitate the amount of human 18s RNA in nasal samples to overcome variability between patient respiratory specimens. We found that this reduced the amount of variation in viral load estimations and reduced the apparent differences between severity groups observed by Buckingham et al 45 and agree with Gueudin et al 46 who also normalized their samples for cell number.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the findings of others that RSV-A is not more severe than RSV-B. 44 We used real-time RT-PCR to quantitate the amount of human 18s RNA in nasal samples to overcome variability between patient respiratory specimens. We found that this reduced the amount of variation in viral load estimations and reduced the apparent differences between severity groups observed by Buckingham et al 45 and agree with Gueudin et al 46 who also normalized their samples for cell number.…”
Section: Discussionsupporting
confidence: 90%
“…This study reports predominance of RSV Group B infection in children hospitalized with CAP, which is not unusual in other regions [9,28]. Unfortunately, our data presents some limitation since we could collect samples for only one year and annual RSV Group epidemic may change.…”
Section: Discussionmentioning
confidence: 85%
“…Infections manifest as mild upper respiratory tract infections (URTI) or lower respiratory tract infections (LRTI), including bronchitis, bronchiolitis, and pneumonia 1–3 . A multi‐year epidemiological study of RSV infections in Croatia has shown that RSV infections have a repeated biennial pattern 4,5 . After a major RSV outbreak beginning in December/January (1994/95, 1996/97, 1998/99, 2000/01, 2002/03, 2004/05 and 2006/07), there ensues a minor one beginning 14–16 months later (March/April peak of 1996, 1998, 2000, 2002, 2004 and 2006), followed again by a major outbreak in another 8–10 months 4–6 .…”
mentioning
confidence: 99%
“…A multi‐year epidemiological study of RSV infections in Croatia has shown that RSV infections have a repeated biennial pattern 4,5 . After a major RSV outbreak beginning in December/January (1994/95, 1996/97, 1998/99, 2000/01, 2002/03, 2004/05 and 2006/07), there ensues a minor one beginning 14–16 months later (March/April peak of 1996, 1998, 2000, 2002, 2004 and 2006), followed again by a major outbreak in another 8–10 months 4–6 . The same biennial pattern of RSV outbreaks was also noted in Germany, Switzerland, Austria, Finland and Sweden 7–12 .…”
mentioning
confidence: 99%